Evidências do conhecimento metacognitivo na tomada de decisão por ser professor de física - Pimentel, Emanuel Cesar (2019)
The research presented starts from the need to analyze the presence of metacognitive thinking in the professional choice of students, considering the importance of this process being guided by conscious processes and supported by elements that favor success in the formative process and in the professional exercise. As a delimitation of the study we adopted as research subjects who chose to take a degree course in Physics from having experienced positive experiences in relation to the discipline during their training process in basic education, specifically in high school. Thus the research is anchored by the following questions: In what context do the positive experiences of students of basic education have repercussions on conscious choices for being a teacher of Physics? To what extent do (or not) evidences of metacognitive knowledge appear in the decision-making of acting as a teacher? By conscious choices we mean those that are accompanied by the evaluation of our own knowledge, that is, they are linked to the metacognitive knowledge as proposed by Flavell and Wellman (1977) and by lived experiences we understand the results of something that impacts and influences the subject as indicated by Larrosa (2016) and Dewey (1979). From these choices we aim to analyze the relationship between the positive experiences in basic education and the activation of metacognitive knowledge in students who choose to take a degree in Physics. For the development of the research, we assumed the qualitative approach, since the focus of the research was associated to the Física-L course at the Universidade de Passo Fundo. The methodological course involved two stages, the first one associated to a questionnaire applied to course participants and allowed to map those who had opte d for it from experiencing positive experiences in relation to Physics during their high school period. In the second stage, interviews were carried out with eight subjects with the objective of verifying if the course option was associated with the evocation of metacognitive thought and in what circuits this occurred. The results allowed to identify that to the choices are associated metacognitive knowledge, however, to different degrees depending on the context in which the positive experience occurred. These results made it possible to infer the importance of the role of the teacher of basic education in the professional choice and reinforced the university context as responsible for the mobilization and identification of the graduates with the teaching c areer.